Lithium ion battery and preparation method thereof
By using a combination of high lithium salt concentration and diluent in the electrolyte of lithium-ion batteries, a stable SEI film and high ion conductivity are formed, which solves the problem of poor circulation performance of lithium-ion batteries under high temperature conditions and improves the battery's Stability and safety.
Patent Information
- Application Number
- CN202411272351.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-24
AI Technical Summary
Existing lithium-ion batteries have poor cycling performance under high temperature conditions, rapid capacity decay and easy to cause heat loss, mainly due to the narrowing of the stable window of the electrolyte and the damage of the SEI film.
The electrolyte with a high lithium salt concentration is used to add diluent before the aging treatment to form an inorganic substance-rich SEI film, and the electrolyte is further diluted through the diluent to improve the ionic conductivity to ensure the stability of the battery cycle.
It significantly improves the stability and circulation performance of lithium-ion batteries in high temperature environments, extends battery life, and enhances the safety performance of the battery.
Smart Images

Figure CN119181862A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrochemical energy storage, and in particular to a lithium ion battery and a preparation method thereof. Background Art
[0002] In the fields of aerospace, atmosphere, drilling, etc., batteries are required to be able to adapt to a variety of temperature conditions. However, there are few reports of commercial lithium-ion batteries with long life and wide temperature range that can achieve long-term stable cycling at both room temperature and high temperature conditions. At present, the cycle life of commercial lithium-ion batteries at room temperature has been significantly improved, reaching 15,000 cycles (70% SOH). However, under high temperature conditions, lithium-ion batteries still have problems such as rapid capacity decay and easy thermal runaway at excessively high temperatures.
[0003] The electrolyte plays a key role in the performance of lithium-ion batteries. High temperature conditions will reduce the LUMO energy level of the solvent in the electrolyte and narrow the stability window of the electrolyte. Compared with normal temperature conditions, the electrolyte is more likely to decompose under high temperature conditions. In addition, according to the Arrhenius equation, the reaction rate doubles for every 10°C increase in temperature, resulting in intensified side reactions in the electrochemical reaction system, and the generated by-products further damage the SEI film. Moreover, under high temperature conditions, the metastable substances of the SEI film components repeatedly undergo a decomposition-growth process, causing a large amount of active lithium to be consumed, ultimately leading to a sharp attenuation of the battery capacity, and the continuously thickened SEI film will also lead to an increase in interfacial impedance, further deteriorating battery performance. Summary of the invention
[0004] Based on this, it is necessary to provide a lithium ion battery and a preparation method thereof to improve the cycle performance of the lithium ion battery under high temperature conditions.
[0005] The first aspect of the present invention is to provide a method for preparing a lithium ion battery, the scheme is as follows:
[0006] A method for preparing a lithium ion battery comprises the following steps:
[0007] Injecting an electrolyte into a bare battery cell to obtain a first battery cell, wherein the electrolyte comprises a lithium salt, a first solvent, and a diluent, and a concentration of the lithium salt in the electrolyte is greater than or equal to 0.6 mol / L;
[0008] Performing a formation aging treatment on the first battery cell to obtain a second battery cell;
[0009] A diluent is injected into the second battery cell, wherein the diluent includes a second solvent.
[0010] In one embodiment, the mass ratio of the electrolyte to the diluent is (4.5-5.5):1.
[0011] In one embodiment, the molar ratio of the diluent to the lithium salt is (1-3):1.
[0012] In one embodiment, the diluent is a fluorine-substituted alkyl ether.
[0013] In one embodiment, the diluent is selected from one or more of bis(2,2,2-trifluoroethyl) ether (BTFE), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) and tris(trifluoroethoxy)methane (TFEO).
[0014] In one embodiment, the first solvent and the second solvent are independently selected from one or more of dimethyl carbonate (DMC), ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC) and triethyl phosphate (TEP).
[0015] In one embodiment, the concentration of the lithium salt in the electrolyte is 0.6 mol / L~3 mol / L.
[0016] In one embodiment, the lithium salt is fluorine-substituted alkylsulfonyl imide lithium.
[0017] In one embodiment, the lithium salt is selected from one or more of lithium bis(fluorosulfonyl)imide (LiFSI), lithium trifluoromethanesulfonylimide (LiTFSI) and lithium bis(pentafluoroethylsulfonyl)imide (LiBETI).
[0018] In one embodiment, the electrolyte further includes a first film-forming additive, and the molar ratio of the first film-forming additive to the lithium salt is (0.01-0.2):1.
[0019] In one embodiment, the first film-forming additive is selected from one or more of vinylene carbonate (VC) and fluoroethylene carbonate (FEC).
[0020] In one embodiment, the diluent further includes a second film-forming additive, and the molar ratio of the second film-forming additive to the second solvent is (0.01-0.04):1.
[0021] In one embodiment, the second film-forming additive is selected from one or more of vinylene carbonate (VC) and fluoroethylene carbonate (FEC).
[0022] The second aspect of the present invention is to provide a lithium ion battery, which is prepared by the preparation method described in any of the above embodiments.
[0023] Compared with the traditional solution, the above lithium ion battery and its preparation method have the following beneficial effects:
[0024] The preparation method of the above-mentioned lithium-ion battery injects an electrolyte with a high lithium salt concentration into the bare battery cell. In the formation stage, the high concentration of lithium salt causes the anion salt in the electrolyte to be preferentially reduced in large quantities, generating an inorganic-rich SEI film, forming an SEI film with more stable properties, and improving the stability of the battery in a high temperature environment. However, too high a lithium salt concentration will also lead to a large polarization of the formation, which is not conducive to the formation of a complete SEI film. Secondly, due to the increase in polarization in the middle and late stages of a long cycle, the battery performance will also decrease. To this end, the above-mentioned preparation method adds a diluent to the electrolyte before the formation aging treatment, so that the electrolyte can form a complete SEI film with stable properties while still having the electrochemical characteristics of a high concentration of lithium salt, thereby improving the stability of the battery in a high temperature environment and improving the cycle performance. In addition, after the formation aging treatment, the electrolyte is further diluted with a diluent including a second solvent, which can improve the electrolyte ion conductivity, ensure that the electrolyte has sufficient ion conductivity in a long cycle, and fully guarantee the stability of the battery cycle process. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] FIG1 is a schematic diagram of a process for preparing a lithium-ion battery according to an embodiment of the present invention;
[0026] FIG2 is a graph showing cycle performance test data of batteries prepared in Examples 1 to 5 and Comparative Examples 1 to 3 at 25° C.;
[0027] FIG3 is a graph showing the cycle performance test data of the batteries prepared in Examples 1 to 5 and Comparative Examples 1 to 3 at 75° C. DETAILED DESCRIPTION
[0028] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are shown in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. The purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0029] In the description of the present invention, it should be understood that the terms "first" and "second" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number or order of the indicated technical features.
[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0031] The invention provides a method for preparing a lithium ion battery.
[0032] As shown in FIG1 , a method 10 for preparing a lithium-ion battery according to an embodiment includes the following steps:
[0033] Step S100, injecting electrolyte into the bare battery cell to obtain a first battery cell. The electrolyte includes lithium salt, a first solvent and a diluent, and the concentration of lithium salt in the electrolyte is greater than or equal to 0.6 mol / L.
[0034] Step S200, performing formation aging treatment on the first battery cell to obtain a second battery cell.
[0035] Step S300: injecting a diluent into the second battery cell, wherein the diluent includes a second solvent.
[0036] The preparation method of the above-mentioned lithium-ion battery injects an electrolyte with a high lithium salt concentration into the bare battery cell. In the formation stage, the high concentration of lithium salt causes the anion salt in the electrolyte to be preferentially reduced in large quantities, generating an inorganic-rich SEI film, forming an SEI film with more stable properties, and improving the stability of the battery in a high temperature environment. However, too high a lithium salt concentration will also lead to a large polarization of the formation, which is not conducive to the formation of a complete SEI film. Secondly, in the middle and late stages of a long cycle, due to the increase in polarization, the battery performance will also decrease. For this reason, the above-mentioned preparation method adds a diluent to the electrolyte before the formation aging treatment, so that the electrolyte still has the electrochemical characteristics of a high concentration of lithium salt. When it can form a complete SEI film with stable properties, the stability of the battery in a high temperature environment is improved, and the cycle performance is improved. In addition, after the formation aging treatment, the electrolyte is further diluted with a diluent including a second solvent, which can improve the electrolyte ion conductivity, ensure that the electrolyte has sufficient ion conductivity in a long cycle, and fully guarantee the stability of the battery cycle process.
[0037] In some examples, the mass ratio of the electrolyte to the diluent is (4.5-5.5) : 1. Further, the mass ratio of the electrolyte to the diluent is (5-5.3) : 1. In some specific examples, the mass ratio of the electrolyte to the diluent is 4.5: 1, 4.6: 1, 4.7: 1, 4.8: 1, 4.9: 1, 5: 1, 5.1: 1, 5.2: 1, 5.3: 1, 5.4: 1, 5.5: 1, etc.
[0038] In some examples, in step S100 , the lithium salt is saturatedly dissolved in the first solvent.
[0039] In some examples, in step S100, the electrolyte has a high concentration of lithium salt of 0.6 mol / L to 3 mol / L. The high concentration of lithium salt forms tight ion pairs or anion-cation aggregates in the solvation structure, allowing more anions to participate in the solvation structure. During the formation process, the preferentially reduced species are transferred from the previous solvent molecules to the anions, thereby generating a more stable SEI film rich in inorganic substances.
[0040] In step S100, the concentration of lithium salt in the electrolyte is 0.6mol / L to 3mol / L. Further, the concentration of lithium salt in the electrolyte is 2mol / L to 3mol / L. In some specific examples, the concentration of lithium salt in the electrolyte is 0.6mol / L, 1.2mol / L, 1.5mol / L, 1.8mol / L, 2mol / L, 2.3mol / L, 2.5mol / L, 2.8mol / L, 3mol / L, etc.
[0041] Optionally, in step S100, the first solvent may be, but is not limited to, one or more of propylene carbonate (PC), butylene carbonate (BC), dimethyl carbonate (DMC), ethylene carbonate (EC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), triethyl phosphate (TEP), γ-butyrolactone, methyl formate, ethyl formate, methyl acetate, ethyl acetate, ethyl propionate, propyl propionate, ethyl butyrate and propyl butyrate.
[0042] In some examples, in step S100 , the first solvent is one or more of dimethyl carbonate (DMC), ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), and triethyl phosphate (TEP).
[0043] In some examples, in step S100, the diluent is a fluorine-substituted alkyl ether. The diluent can play a dilution role without participating in the solvation of lithium ions and changing the solvation structure of high-concentration lithium salts, so that the diluted electrolyte still has the electrochemical characteristics of high-concentration lithium salts.
[0044] Further, in some examples, the diluent is one or more of bis(2,2,2-trifluoroethyl) ether (BTFE), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) and tris(trifluoroethoxy)methane (TFEO).
[0045] In some examples, in step S100, the molar ratio of the diluent to the lithium salt is (1-3):1. The diluent can dilute the lithium salt more effectively, while allowing the electrolyte to still have the electrochemical characteristics of a high concentration of lithium salt. In some examples, the molar ratio of the diluent to the lithium salt is 1:1, 1.3:1, 1.5:1, 1.8:1, 2:1, 2.3:1, 2.5:1, 2.8:1, 3:1, etc.
[0046] Optionally, in step S100, the lithium salt may be one or more of, but not limited to, LiPF6, LiBF4, LiClO4, LiAsF6, LiCF3SO3, LiN(CF3SO2)2, LiBOB, LiDFOB, LiFSI, LiTFSI and LiBETI.
[0047] Furthermore, in some examples, the lithium salt uses fluorine-substituted alkylsulfonyl imide lithium. Compared with other lithium salts, this type of lithium salt is extremely soluble in solvents and will not precipitate. In addition, it has high thermal stability and is not easy to decompose. Therefore, it is more suitable for configuring high-concentration lithium salt electrolytes and high-temperature application systems.
[0048] Further, in some examples, the lithium salt is one or more of lithium bis(fluorosulfonyl)imide (LiFSI), lithium trifluoromethanesulfonylimide (LiTFSI), and lithium bis(pentafluoroethylsulfonyl)imide (LiBETI).
[0049] In some examples, in step S100, the electrolyte further includes a first film-forming additive. The molar ratio of the first film-forming additive to the lithium salt is (0.01-0.2):1. By adding the first film-forming additive to the electrolyte, it is beneficial to form a more complete SEI film and repair the SEI film damaged during the cycle. In some examples, in some examples, the molar ratio of the first film-forming additive to the lithium salt is 0.01:1, 0.02:1, 0.04:1, 0.06:1, 0.08:1, 0.1:1, 0.15:1, 0.2:1, etc.
[0050] Optionally, the first film-forming additive may be, but is not limited to, one or more of vinylene carbonate (VC) and fluoroethylene carbonate (FEC).
[0051] In some examples, in step S200, the formation process temperature is set to 45°C to 65°C, preferably using a gradient formation method.
[0052] In some examples, the formation aging process includes the following steps:
[0053] Charge at a constant current of 0.01-0.05C to 2-5% SOC, and let it stand for 5-15 minutes.
[0054] Charge at a constant current of 0.05-0.1C to 10-15% SOC, and let it stand for 5-15 minutes.
[0055] Charge at 0.1C constant current to 20-30% SOC, and let stand for 5-15 minutes;
[0056] Charge at 0.2C constant current to 45-65% SOC, and let stand for 5-15 minutes;
[0057] The battery is formed to 100% SOC at 0.33C constant current and constant voltage, and then allowed to stand for 20 to 40 minutes;
[0058] Aging the formed cells at 45-65°C for 24-48 hours.
[0059] Optionally, in step S300, the second solvent may be, but is not limited to, one or more of propylene carbonate (PC), butylene carbonate (BC), dimethyl carbonate (DMC), ethylene carbonate (EC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), triethyl phosphate (TEP), γ-butyrolactone, methyl formate, ethyl formate, methyl acetate, ethyl acetate, ethyl propionate, propyl propionate, ethyl butyrate and propyl butyrate.
[0060] In some examples, in step S300 , the second solvent is one or more of dimethyl carbonate (DMC), ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), and triethyl phosphate (TEP).
[0061] Optionally, the first solvent and the second solvent may be the same or different.
[0062] In some examples, in step S200, the diluent further includes a second film-forming additive. The molar ratio of the second film-forming additive to the second solvent is (0.01-0.04):1. Adding the second film-forming additive is conducive to forming a more complete SEI film and repairing the SEI film damaged during the cycle. In some examples, the molar ratio of the second film-forming additive to the second solvent is 0.01:1, 0.015:1, 0.02:1, 0.025:1, 0.03:1, 0.035:1, 0.04:1, etc.
[0063] Optionally, the second film-forming additive may be, but is not limited to, one or more of vinylene carbonate (VC) and fluoroethylene carbonate (FEC).
[0064] Optionally, the first film-forming additive and the second film-forming additive may be the same or different.
[0065] Usually, the design of high-temperature battery systems requires that the negative electrode graphite has a large particle size and a small specific surface area to reduce parasitic reactions at high temperatures, but this will bring about the problem of insufficient reaction kinetics. However, the present invention adds a diluent to the electrolyte before the formation and aging treatment, and the electrolyte still has the electrochemical characteristics of a high-concentration lithium salt. After the formation and aging treatment, the electrolyte is diluted with a diluent including a second solvent, which can improve the electrolyte ion conductivity and largely resolve this contradiction. Due to the special solvation structure, the electrolyte of the present invention can also improve the safety performance of the battery.
[0066] It can be understood that the above-mentioned bare battery cell includes a shell, a positive electrode sheet, a negative electrode sheet and a separator. The positive electrode sheet, the negative electrode sheet and the separator are arranged in the shell. The positive electrode sheet and the negative electrode sheet are arranged opposite to each other. The separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role.
[0067] When preparing the above-mentioned bare battery cell, the positive electrode sheet, the separator and the negative electrode sheet are stacked so that the separator is located between the positive electrode sheet and the negative electrode sheet, and then wound and shelled to obtain the bare battery cell.
[0068] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer arranged on the positive electrode current collector.
[0069] Illustratively, the positive electrode current collector includes metal foil such as aluminum foil and copper foil.
[0070] The positive electrode active material layer contains a positive electrode active material. Exemplarily, the positive electrode active material includes one or more of lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, and lithium nickel cobalt manganese oxide.
[0071] It is understood that the positive electrode active material layer may further include a positive electrode binder, a positive electrode conductor, etc. Exemplarily, the positive electrode binder includes one or more of polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, polyvinyl fluoride, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, epoxy resin, and nylon. Exemplarily, the positive electrode conductor includes one or more of graphite, carbon black, acetylene black, and Ketjen black.
[0072] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer arranged on the negative electrode current collector.
[0073] Illustratively, the negative electrode current collector includes metal foil such as aluminum foil and copper foil.
[0074] The negative electrode active material layer contains a negative electrode active material. Exemplarily, the negative electrode active material includes one or more of natural graphite, artificial graphite, soft carbon, hard carbon, lithium metal, lithium metal alloy and transition metal oxide.
[0075] It is understood that the negative electrode active material layer may further include a negative electrode binder, a negative electrode conductor, etc. Exemplarily, the negative electrode binder includes one or more of polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, polyvinyl fluoride, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, epoxy resin, and nylon. Exemplarily, the negative electrode conductor includes one or more of graphite, carbon black, acetylene black, and Ketjen black.
[0076] The positive electrode sheet and the negative electrode sheet can be prepared by mixing and dispersing the corresponding active material, binder and conductive agent in a solvent to obtain a slurry, then coating the slurry on the corresponding current collector, and then drying to remove the solvent to form a corresponding active material layer on the current collector.
[0077] The diaphragm includes a polymer film material. For example, the polymer film material includes one or more of polyethylene and polypropylene. The diaphragm can be a single-layer diaphragm or a multi-layer diaphragm.
[0078] Furthermore, the present invention also provides a lithium-ion battery, which is prepared by any of the preparation methods in the above examples.
[0079] The following specific examples are provided to further illustrate the present invention. The present invention provides the following specific examples for a better understanding of the present invention, but is not limited to the specific implementation methods and does not limit the protection scope of the present invention.
[0080] Example 1
[0081] This embodiment provides a method for preparing a lithium ion battery, comprising the following steps:
[0082] Preparation of positive electrode:
[0083] The positive electrode active material lithium iron phosphate, binder and conductive agent are dissolved in NMP (N-methylpyrrolidone) at a weight fraction of 96:2:2 to obtain a positive electrode slurry. The positive electrode slurry is coated on aluminum foil. After rolling, slitting and other processes, and then vacuum dried at 90°C for 8 hours, a positive electrode sheet is obtained.
[0084] Preparation of negative electrode sheet:
[0085] The negative electrode active material artificial graphite, the conductive agent, the thickener and the binder were mixed in a mass ratio of 96.2:2:0.8:1, deionized water was added, and vacuum stirring was performed to obtain a negative electrode slurry.
[0086] The negative electrode slurry is evenly coated on the negative electrode copper foil. The coated copper foil is dried at high temperature, rolled, slit and other processes, and then vacuum dried at 120° C. for 12 hours to obtain a negative electrode sheet.
[0087] Preparation of electrolyte:
[0088] Film-forming additives vinylene carbonate (VC), lithium salt lithium bis(fluorosulfonyl)imide (LiFSI) and diluent bis(2,2,2-trifluoroethyl) ether (BTFE) are dispersed in solvent dimethyl carbonate (DMC), and the molar ratio of VC, LiFSI, DMC and BTFE is 0.05:0.51:1.1:2.2 to obtain an electrolyte.
[0089] Preparation of diluent:
[0090] Vinylene carbonate (VC), a film-forming additive, is dispersed in ethylene carbonate (EC), a solvent, with the molar ratio of VC to EC being 0.02:1, to obtain a diluted solution.
[0091] Lithium-ion battery assembly:
[0092] The positive electrode sheet, the separator and the negative electrode sheet are stacked in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain a bare cell. After welding the pole lugs, the obtained bare cell is placed in the aluminum-plastic film of the outer packaging. The first liquid injection is performed into the bare cell, and 995g of the above-prepared electrolyte is injected to obtain the first cell.
[0093] Performing a formation treatment on the first battery cell to obtain a second battery cell.
[0094] The formation process temperature is set to 50°C, and specifically includes the following steps:
[0095] Charge at 0.03C constant current to 2% SOC and let stand for 10 minutes;
[0096] Charge to 10% SOC at 0.1C constant current and let stand for 10 minutes;
[0097] Charge to 20% SOC at 0.1C constant current and let stand for 10 minutes;
[0098] Charge at 0.2C constant current to 45% SOC and let stand for 10 minutes;
[0099] At 0.33C constant current and constant voltage, the battery was charged to 100% SOC and allowed to stand for 30 minutes.
[0100] The formed cells were aged at 50°C for 40 h.
[0101] Inject 190 g of the diluted solution prepared above into the second battery cell.
[0102] Example 2
[0103] The steps of this embodiment are basically the same as those of Embodiment 1, with the only difference being that the electrolyte includes a film-forming additive vinylene carbonate (VC), a lithium salt lithium bis(fluorosulfonyl)imide (LiFSI), a solvent vinyl carbonate (EC), a solvent dimethyl carbonate (DMC), and a diluent bis(2,2,2-trifluoroethyl) ether (BTFE), and the molar ratio of VC, LiFSI, EC, DMC, and BTFE is 0.05:0.51:0.22:0.88:2.
[0104] Example 3
[0105] The steps of this embodiment are basically the same as those of embodiment 1, with the only difference being that the mass of the diluent injected into the second battery cell is 200 g.
[0106] Example 4
[0107] The steps of this embodiment are basically the same as those of embodiment 1, with the only difference being that the mass of the diluent injected into the second battery cell is 220 g.
[0108] Example 5
[0109] The steps of this embodiment are basically the same as those of Embodiment 1, except that 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) is used as the diluent in the electrolyte.
[0110] Comparative Example 1
[0111] The steps of this comparative example are basically the same as those of Example 1, except that the electrolyte includes DMC, EC and VC in a mass ratio of 40:56:4, and the lithium salt is 1 mol / L LiFSI.
[0112] Comparative Example 2
[0113] The difference between this comparative example and Example 1 is that only one injection is performed, that is, no diluent is injected after the chemical formation treatment.
[0114] Comparative Example 3
[0115] The steps of this comparative example are basically the same as those of Example 1, except that no diluent bis(2,2,2-trifluoroethyl) ether (BTFE) is added to the electrolyte.
[0116] The conductivity of the electrolyte after the secondary injection was tested, wherein the conductivity of the electrolyte after the formation treatment was tested in Comparative Example 2. The test results are shown in Table 1.
[0117] Table 1. Electrolyte conductivity test
[0118]
[0119] It can be seen from the test results in Table 2 that the conductivity of the electrolyte after the secondary injection of Example 1 is much greater than the conductivity of the electrolyte after the formation treatment of Comparative Example 2, indicating that the ionic conductivity of the electrolyte can be significantly improved by injecting a diluent into the secondary injection after the battery cell formation treatment.
[0120] The lithium-ion batteries prepared in the above examples and comparative examples were subjected to safety performance tests and electrochemical performance tests.
[0121] The specific methods of safety performance testing are as follows:
[0122] The lithium-ion batteries prepared in the above-mentioned embodiments and comparative examples were subjected to an overcharge test. After being charged to 5.5 V at 1C, the batteries were left to stand for 1 hour to observe whether the lithium-ion batteries swelled, leaked, smoked, caught fire or exploded.
[0123] The results of the safety performance test are shown in Table 2.
[0124] The electrochemical performance test method is as follows:
[0125] The lithium-ion batteries prepared in the above embodiments and comparative examples were subjected to cycle tests according to the following steps: the lithium-ion batteries were placed in a constant temperature box with a set temperature (divided into room temperature and high temperature), and after standing for 2 hours, a cycle test was performed, 0.5P to 3.65V, standing for 10 minutes, 0.5P DP to 2.5V, and standing for 10 minutes.
[0126] The set temperature of the normal temperature performance test group was 25°C, and the test results are shown in Figure 2. The set temperature of the high temperature performance test group was 75°C, and the test results are shown in Figure 3.
[0127] Table 2. Overcharge test results
[0128]
[0129] It can be seen from the test results in Table 2 that, compared with Comparative Example 1, the high-voltage safety performance of the other groups is improved, indicating that the local high-concentration electrolyte and the diluted local high-concentration electrolyte have higher safety performance.
[0130] Figures 2 and 3 show that the cycle performance of the embodiment group at room temperature and high temperature is much better than that of the comparative example group, indicating that compared with the traditional electrolyte, the diluted local high-concentration electrolyte can not only improve the room temperature cycle performance, but also greatly improve the high-temperature long-cycle stability of the battery.
[0131] In summary, the preparation method of the present invention can not only greatly improve the safety performance of lithium-ion batteries, but also improve the cycle stability at room temperature and high temperature, broaden the application temperature window of lithium-ion batteries, and has great application prospects.
[0132] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0133] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a lithium ion battery, characterized in that: The following steps are involved: Injecting an electrolyte into a bare battery cell to obtain a first battery cell, wherein the electrolyte comprises a lithium salt, a first solvent, and a diluent, and a concentration of the lithium salt in the electrolyte is greater than or equal to 0.6 mol / L; Performing a formation aging treatment on the first battery cell to obtain a second battery cell; A diluent is injected into the second battery cell, wherein the diluent includes a second solvent.
2. The preparation method according to claim 1, characterized in that The mass ratio of the electrolyte to the diluent is (4.5-5.5):
1.
3. The preparation method according to claim 1, characterized in that: The molar ratio of the diluent to the lithium salt is (1-3):
1.
4. The preparation method according to claim 1, characterized in that: The diluent is a fluorine-substituted alkyl ether.
5. The preparation method according to claim 4, characterized in that: The diluent is selected from one or more of bis(2,2,2-trifluoroethyl) ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether and tris(trifluoroethoxy)methane.
6. The preparation method according to claim 1, characterized in that: The first solvent and the second solvent are independently selected from one or more of dimethyl carbonate, ethylene carbonate, propylene carbonate, ethyl methyl carbonate and triethyl phosphate.
7. The preparation method according to claim 1, characterized in that: The concentration of the lithium salt in the electrolyte is 0.6 mol / L to 3 mol / L.
8. The preparation method according to claim 1, characterized in that: The lithium salt is fluorine-substituted alkylsulfonyl imide lithium.
9. The preparation method according to claim 8, characterized in that: The lithium salt is selected from one or more of lithium bis(fluorosulfonyl)imide, lithium trifluoromethanesulfonylimide and lithium bis(pentafluoroethylsulfonyl)imide.
10. The preparation method according to any one of claims 1 to 9, characterized in that: The electrolyte further includes a first film-forming additive, and a molar ratio of the first film-forming additive to the lithium salt is (0.01-0.2):
1.
11. The preparation method according to claim 10, characterized in that: The first film-forming additive is selected from one or more of vinylene carbonate and fluoroethylene carbonate.
12. The preparation method according to any one of claims 1 to 9 and 11, characterized in that: The diluent further includes a second film-forming additive, and the molar ratio of the second film-forming additive to the second solvent is (0.01-0.04):
1.
13. The preparation method according to claim 12, characterized in that: The second film-forming additive is selected from one or more of vinylene carbonate and fluoroethylene carbonate.
14. A lithium ion battery, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 13.
